Patient Perspectives Highlight Barriers to Telehealth Adoption Beyond Internet Access. - Schultheis, Luke (ONS Voice, 2026)
Both groups preferred in-person care for its perceived thoroughness and comfort, trust, and emotional connection. The researchers said that lack of confidence and unfamiliarity with VTV platforms were primary adoption barriers, rather than technology access and literacy. Some patients in both groups avoided VTVs because of concerns about the quality of telehealth visits.